Leaving time [compact disc, unabridged] : a novel - Picoult, Jodi, 1966- (Random House Audio, 2014)
For more than a decade, Jenna Metcalf has searched for her mother, Alice, who mysteriously disappeared after a tragic accident. Desperate to find the truth, Jenna enlists two unlikely allies in her quest. Serenity Jones is a psychic who rose to fame finding missing persons. Virgil Stanhope is a jaded private detective who originally investigated Alice's case. As they work together to uncover the truth, they realize that in asking hard questions, they'll have to face even harder answers.